EFEKTIVITAS PENGGUNAAN JENIS MADU YANG BERBEDA PADA MASKULINISASI IKAN CUPANG (Betta sp.) DENGAN METODE PERENDAMAN INDUK - Abdani, Reza Maulana; Marzuki, Muhammad; Scabra, Andre Rachmat (JARI : Jurnal Akuakultur Rawa Indonesia, 2023)
Cupang fish (Betta sp.) are included in the variety of freshwater ornamental fish with attractive and beautiful colors and bodies. However, male betta fish are more desirable. The purpose of this study was to determine the effect of immersing betta fish (Betta sp) broodstock using three different types of honey on the percentage of male fish through broodstock immersion. This study used a completely randomized design (CRD) with 4 treatments and 3 replications, namely P0 (control), P1 (forest honey), P2 (livestock honey), and P3 (mangrove honey), so there were 12 experimental units. Analysis of the percentage of male sex was carried out using analysis of variance (ANOVA) and Duncan's test. The calculation results show that the percentage of male fish in forest honey, livestock honey, and mangrove honey are 76%, 74%, and 92%, respectively. The results of the calculation of the survival rate ranged from 50 – 53%, the fecundity value ranged from 160 – 245 eggs, the hatching rate ranged from 53 – 58%, the absolute weight growth showed a relatively similar value, namely 0.61 – 0.70g, and the weight growth specifically shows a value of 2.84 - 2.90%. The water quality parameter values of temperature, pH and DO obtained during the study were still in optimal conditions for betta fish maintenance. Thus it can be concluded that the treatment using mangrove honey is the treatment with the highest effectiveness value for directing the sex of betta fish (Betta sp) to male.